Are prophylactic antibiotics necessary for urodynamic study?. Issue 6 (22nd December 2012) - Gürbüz, Cenk; Güner, Bayram; Atış, Gökhan; Canat, Lütfi; Caşkurlu, Turhan
Abstract: The aim of this study was to assess the efficacy of prophylactic fosfomycin tromethamine (FT) and ciprofloxacin in preventing bacteriuria caused by urodynamic studies (UDS). A total of 426 adult patients presenting for UDS were enrolled the study. A midstream urine sample was taken 72 hours before and 5 days after the procedure. All patients underwent a standard UDS. The 411 patients who had sterile urine before intervention were included in the study. Patients were randomized into three groups. Group1 received no prophylaxis ( n = 133), Group 2 ( n = 141) received oral ciprofloxacin (500 mg) 1 hour before the procedure, and Group 3 ( n = 137) received a single dose of FT approximately 12 hours before the procedure. Bacteriuria was evaluated for each group. Bacteriuria was detected in 3 (2.3%), 6 (4.3%) and 3 patients (1.6%) in Group 1, Group 2, and Group 3, respectively. The most common identified microorganism was Escherichia coli (E coli) in 6 patients (50%). Among the E coli group, extended spectrum beta‐lactamase producing E coli was seen in 2 patients (33.3%). Univariate analysis demonstrated that a history of urogenital operation ( p < 0.01) and female gender ( p < 0.01) were significant risk factors for bacteriuria. On multiple logistic regression analysis, the past urogenital operation history was the only significant independent risk factor for significant bacteriuria after UDS (OR = 14, 95% CI = 1.82–23.8, p = 0.01). The prevalence of bacteriuria after UDS was relatively low in the current study population. Therefore, for most patients, it may be unnecessary to use preventive prophylactic antibiotics. However, our results suggest that in patients with a previous history of urologic surgery, the risk for significant bacteriuria is increased and the use of prophylaxis should be considered.